2005
DOI: 10.1007/s11096-005-6034-x
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Errors with Cytotoxic Drugs and the Inadequacy of Existing Classifications

Abstract: The 349 detected errors involved mainly the physicochemical properties of preparations. A computerised prescription network could possibly reduce the number of such errors. Furthermore, a redefinition of the classifications of errors for cytotoxic preparations seems desirable, and such classifications should include typical pharmaceutical problems, and potential errors that do not reach the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
4
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 10 publications
(4 reference statements)
2
19
4
4
Order By: Relevance
“…The rate of interventions in the present study, 22% during prescription screening and 4% during drug release, was higher than the rate of medication errors identified in chemotherapy prescription orders reported in the literature 9,11. Markert et al reported a chemotherapy error in 17.1% of received chemotherapy orders9, while Slama et al reported a prescribing error in 12% of the received chemotherapy orders 11.…”
Section: Discussioncontrasting
confidence: 72%
See 4 more Smart Citations
“…The rate of interventions in the present study, 22% during prescription screening and 4% during drug release, was higher than the rate of medication errors identified in chemotherapy prescription orders reported in the literature 9,11. Markert et al reported a chemotherapy error in 17.1% of received chemotherapy orders9, while Slama et al reported a prescribing error in 12% of the received chemotherapy orders 11.…”
Section: Discussioncontrasting
confidence: 72%
“…Markert et al reported a chemotherapy error in 17.1% of received chemotherapy orders9, while Slama et al reported a prescribing error in 12% of the received chemotherapy orders 11. However, the majority of errors in the described studies, 50.9% and 74%, respectively, were related to problem categories not included herein: missing a patient’s informed consent; and physicochemical incompatibilities.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations